Examining the Structural Relationships Between Pre-Service Science Teachers’ Intention to Teach and Perceptions of the Nature of Science and Attitudes - Alazzam Sulaf; AlEeassa Mohammad; Alquraan Mahmoud; Almughrabi Ayat (Open Education Studies, 2024)
The current study aimed to examine the structural relationships between pre-service science teachers’ intention to teach and perceptions of the nature of science (NOS) and attitudes toward teaching science. The sample consisted of 206 pre-service science teachers from a major university in the United Arab Emirates who have bachelor’s degrees in science. Quantitative research methodology was used to study the structural relationships among pre-service science teachers’ intention to teach, perceptions of the NOS, and attitudes. Structural equation modeling using the Lavaan package was used to test these structural relationships. The results show that the relationships between the indigenous constructs (NOS) and the mediator constructs (DAS) can predict pre-service science teachers’ intention to teach science (p < 0.05).